What is Needed for Evidence‐Based Dietary Recommendations for Migraine: A Call to Action for Nutrition and Microbiome Research. Issue 9 (11th October 2019) - Slavin, Margaret; Li, Huilun (Amber); Frankenfeld, Cara; Cheskin, Lawrence J.
Abstract : Background: The gastrointestinal symptoms of migraine attacks have invited numerous dietary hypotheses for migraine etiology through the centuries. Substantial efforts have been dedicated to identifying dietary interventions for migraine attack prevention, with limited success. Meanwhile, mounting evidence suggests that the reverse relationship may also exist – that the biological mechanisms of migraine may influence dietary intake. More likely, the truth involves some combination of both, where the disease influences food intake, and the foods eaten impact the manifestations of the disease. In addition, the gut's microbiota is increasingly suspected to influence the migraine brain via the gut‐brain axis, though these hypotheses remain largely unsubstantiated. Objective: This paper presents an overview of the strength of existing evidence for food‐based dietary interventions for migraine, noting that there is frequently evidence to suggest that a dietary risk factor for migraine exists but no evidence for how to best intervene; in fact, our intuitive assumptions on interventions are being challenged with new evidence. We then look to the future for promising avenues of research, notably the gut microbiome. Conclusion: The evidence supports a call to action for high‐quality dietary and microbiome research in migraine, both to substantiate hypothesized relationships and build the evidence base regarding nutrition's potential impact on migraine attack prevention and treatment.